Analisis Kinerja Karyawan dengan Motivasi Berprestasi Sebagai Variabel Intervening pada Direktorat Operasi PT. Semen Padang - Esron Tarigan (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to test an extensive effect of transformational leadership, and organizational culture on the performance of employees with achievement motivation as the variable intervening comes home PT Semen Padang. Methods of collecting data through surveys and circulating kingdom, with a sample of 100 respondents. The analytical method used is path analysis using STATISTIC SPSS 25. The results of the study were obtained transformational leadership had a positive and significant effect on motivation to face faculty faced. Organizational culture has a positive and significant effect on achievement motivation. Transformational leadership has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance. Disconnecting motivation has a positive and insignificant effect on employee performance. Achieving motivation does not mediate transformational leadership on employee performance. Achieving motivation does not mediate organizational culture on employee performance. The contribution of the independent variable contribution of transformational leadership, organizational culture, and motivation faced variables depends on the performance of 85.7%. While the rest is 14.3% influenced by other variables outside of this study